Aspherical Supernovae and Oblique Shock Breakout. Issue Volume 12:Issue S331(2017) (17th October 2017) - Afsariardchi, Niloufar; Matzner, Christopher D.
Abstract: In an aspherical supernova explosion, shock emergence is not simultaneous and non-radial flows develop near the stellar surface. Oblique shock breakouts tend to be easily developed in compact progenitors like stripped-envelop core collapse supernovae. According to Matzner et al. (2013), non-spherical explosions develop non-radial flows that alters the observable emission and radiation of a supernova explosion. These flows can limit ejecta speed, change the distribution of matter and heat of the ejecta, suppress the breakout flash, and most importantly engender collisions outside the star. We construct a global numerical FLASH hydrodynamic simulation in a two dimensional spherical coordinate, focusing on the non-relativistic, adiabatic limit in a polytropic envelope to see how these fundamental differences affect the early light curve of core-collapse SNe.